Routine use of Zenit RA, a novel chemiluminescent immunoanalyzer in autoimmune disease diagnosis - Ghillani, P.; Dufat, L.; Himeur, S.; Miyara, M.; Amoura, Z.; Musset, L. (Autoimmunity highlights, 2012)
The detection of antibodies is useful to diagnose and/or to classify autoimmune diseases as connective tissue diseases and vasculitis. Zenit RA is a fully automated immunoanalyzer. The aim of this study was to compare the predictive and discriminative performance of the Zenit RA anti-cyclic citrullinated peptide (CCP), anti-cardiolipin (aCL) and anti-β 2 glycoprotein 1 (aB2GP1) tests to conventional ELISAs on clinically well-defined groups of patients and to daily evaluate the determination of anti-extractable nuclear antigen (ENA), anti-double stranded DNA (dsDNA), anti-myeloperoxidase (MPO) and anti-proteinase 3 (PR3) antibodies in a hospital laboratory. Reagents available on Zenit RA analyzer exhibit good diagnostic performances, regarding sensitivity, specificity, positive and negative predictive values. Global agreements between Zenit RA and conventional tests were from 90 to 98 % (Kappa-values ranging 0.56–0.94): 96 % for anti-CCP, 90–94 % for aCL and aB2GP1, 94 % for anti-dsDNA, 97 % for anti-ENA, 98 % for anti-MPO and 95 % for anti-PR3 antibodies. Zenit RA analyzer is easy to rapidly detect the most common autoantibodies in autoimmune diseases. This system has a potential to provide clinically useful data within a short time. Because of the flexibility of its work modalities, it is well adapted to determine antigenic specificities in daily practice.